Effect of laser irradiation on structural and optical Properties of ZnO thin films prepared by sol-gel method - Khudiar, Ausama I. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Zinc oxide thin films were prepared by sol-gel process. The sol was prepared from zinc acetate dehydrate. Methoxyethanol and monoethanolamine were used as solvent and stabilizer, respectively. Structuralinvestigation including microstructure was carried out by X-ray diffraction (XRD) analysis. The films give a hexagonal wurtzite structure with diffraction peaks at (100), (002) and (101). It is found that theparticle size of the films change after N2 laser irradiation. Optical properties of the thin films were determined by using UV-VIS-NIR spectrometer. It was found that the band gap of the thin films decreased from 3.16 eV to 2.6 eV after N2 laser irradiation. Such films can be applied on silicon solarcells as the changes in the band gap are acceptable as a requirement for good anti-reflecting coating element.